Managing performance and winning trust: how World Bank staff shape recipient performance - Mirko Heinzel; Andrea Liese (The Review of International Organizations, 2021)
World Bank evaluations show that recipient performance varies substantially between different projects. Extant research has focused on country-level variables when explaining these variations. This article goes beyond country-level explanations and highlights the role of World Bank staff. We extend established arguments in the literature on compliance with the demands of International Organizations (IOs) and hypothesize that IO staff can shape recipient performance in three ways. First, recipient performance may be influenced by the quality of IO staff monitoring and supervision. Second, the leniency and stringency with which IO staff apply the aid agreement could improve recipient performance. Third, recipient performance may depend on whether IO staff can identify and mobilize supportive interlocutors through their networks in the recipient country. We test these arguments by linking a novel database on the tenure of World Bank task team leaders to projects evaluated between 1986 and 2020. The findings are consistent with the expectation that World Bank staff play an important role, but only in investment projects. There is substantial evidence that World Bank staff supervisory ability and country experience are linked to recipient performance in those projects. Less consistent evidence indicates that leniency could matter. These findings imply that World Bank staff play an important role in facilitating implementation of investment projects.
Keywords: 320; World Bank; International bureaucrats; Recipient performance; Enforcement; Supervision; Country experience; Compliance